KAJIAN ALTERNATIF PENANGGULANGAN BANJIR (STUDI KASUS SUNGAI LADAPA DI KABUPATEN GORONTALO) - Sarminingsih, Anik (Universitas Diponegoro, 2007)
Flood mitigation is a part of water resources management widely with scope are consist of conservation, controlled and water used. The concept of water controlled is called Flood Control or Flood Mitigation/Flood Damage Mitigation. There are two kinds of flood control, structural and non structural effort. Structural effort is an effort which tends to engineering technique which is aimed to modification the flood discharge and the stage of flood damage. Flood discharge (Q, m3/sec) is the function of velocity (V, m/sec) and cross section area of the river/channel (A, m2). Efforts of flood control can be carried out by justified of the third components. Non-structural effort is aimed to avoid and press the problem that caused by flood with some activities like arrangement of flood plain and watershed development. Non-structural effort usually is conducted for long period goal. Therefore carrying this effort need consistency all of stakeholder. Participatory approach from stakeholder is the key of success of non structural effort.